Patient Satisfaction Road Based On Administration Procedure And Behavior Of Health Officers - Muhammad Ali Sodik; Ice Marselina Sila (Journal of Global Research in Public Health, 2022)
In carrying out its function as a health-oriented development center, a community empowerment center, a primary health care center, and a primary individual health service center, the puskesmas is required to provide mandatory health efforts and development health efforts. The purpose of this study was to analyze the effect of administrative procedures and behavior of officers on maternal and child health polices on outpatient satisfaction at UPTD Puskesmas Nimasi, North Central Timor Regency. The design of this study was an observational quantitative study with a cross sectional approach with the focus of the research directed to be to analyze the effect of administrative procedures and behavior of officers on maternal and child health polices on outpatient satisfaction at the UPTD Puskesmas Nimasi, North Central Timor Regency with a population of 350 respondents and samples as many as 42 respondents were taken by accidental sampling technique. The findings found that nearly half of respondents had administrative procedures in the sufficient category of 19 respondents (45.2%). In addition, almost half of the respondents had sufficient behavioral categories of 20 respondents (47.6%). And also the majority of respondents had a quite satisfied category satisfaction of 22 respondents (52.3%). The results of the study using the Multiple Linear Regression Test showed that with a p-value of 0,000 <0.05, H1 was accepted so it was concluded that there was simultaneously an effect of administrative procedures and the behavior of officers on maternal and child health polices on outpatient satisfaction at UPTD Puskesmas Nimasi District North Central Timor with 76.9% influence. It is expected that outpatients can provide criticism and input related to services expected by patients when conducting health checks at the health center.